Financial vs. Physical Resources: Comparing the Effects of Operational Budget Allocation and School Facility Adequacy on Student Learning Outcomes in Banyuasin Regency - Sudarisman Sudarisman; Rohana Rohana; Andi Rahman (Journal of Social Work and Science Education, 2027)
This study aims to determine and analyze the influence of infrastructure and school operational assistance on the quality of learning at state elementary schools in Karang Agung Ilir District, Banyuasin Regency, both partially and simultaneously. A quantitative method with an ex post facto approach was employed, involving 91 teachers as the sample. Data were collected through questionnaires and documentation, with analysis conducted using the SPSS program. The findings conclude that: (1) infrastructure significantly influences learning quality; (2) school operational assistance significantly influences learning quality; and (3) simultaneously, both infrastructure and operational assistance exert a significant influence on learning quality at the state elementary schools in the district. This study offers empirical evidence from a less-accessible district context, demonstrating the combined explanatory power of physical resources and financial support on learning outcomes in an under-researched rural setting. Findings underscore the necessity for district policymakers to ensure equitable allocation of both infrastructure development funds and operational assistance to sustain and elevate learning quality, particularly in geographically challenged areas. This research contributes actionable insights for educational stakeholders, affirming that simultaneous investment in physical facilities and school operational funding is essential for optimizing learning quality. The results provide a foundational reference for resource distribution strategies aimed at narrowing inter-school quality gaps in similar rural Indonesian elementary education contexts.